High attack frequency in patients with angioedema due to C1-inhibitor deficiency is a major determinant in switching to home therapy: a real-life observational study. Issue 1 (December 2016) - Squeglia, Veronica; Barbarino, Alessandro; Bova, Maria; Gravante, Carmela; Petraroli, Angelica; Spadaro, Giuseppe; Triggiani, Massimo; Genovese, Arturo; Marone, Gianni
Abstract Background Hereditary angioedema with C1-inhibitor deficiency (C1-INH-HAE) is characterized by recurrent attacks of swelling that affect various body sites. Such attacks are a frequent cause of visits to the emergency department and are often treated in the hospital. In recent years, self-administration of C1-inhibitor (C1-INH) concentrates at home has become an increasingly used option, with a positive impact on patient outcomes and quality of life. Methods This was an observational study of 6 months' duration in 56 patients with C1-INH-HAE referred to a HAE center in southern Italy. The patients received three types of treatment for their swelling attacks: C1-INH concentrates administered at home (n = 25); icatibant administered at home (n = 12); and C1-INH concentrates administered in the hospital (n = 19). The objectives of this observational study were to compare therapy compliance (defined as the proportion of treated attacks) and quality of life in home- and hospital-treated patients, and to identify factors associated with the decision to use home therapy. Results Overall, 918 attacks were reported over 6 months, of which 544 (59.2 %) were treated. Total number of reported attacks and the mean (±SD) number of attacks per patient, respectively, in the three groups were: 611 and 24.4 (±26.1) for home-based C1-INH; 191 and 15.9 (±12.0) for home-based icatibant; 166 and 6.1 (±6.5) for hospital-based C1-INH. Differences in attack frequency between home- and hospital-based treatments were statistically significant (p = 0.002), while patient demographic characteristics and the disease severity score did not correlate with the use of home therapy. Compliance with therapy was significantly better with home-based therapy (71.2 % of treated attacks with C1-INH and 44.0 % with icatibant) than with hospital-based therapy (21.6 %, p = 0.003). Quality of life showed an opposite trend, with patients on hospital-based treatment reporting the highest quality of life. Conclusions Home-based therapy was associated with better compliance compared with hospital-based therapy. The choice to adopt home-based therapy appeared to correlate with a high attack frequency. Home-based therapy is a valid treatment option for patients with C1-INH-HAE and should be offered to all such patients, and especially to those with high attack frequency.